A calcar collar is protective against early periprosthetic femoral fracture around cementless femoral components in primary total hip arthroplasty: a registry study with biomechanical validation. (July 2019) - Lamb, J. N.; Baetz, J.; Messer-Hannemann, P.; Adekanmbi, I.; van Duren, B. H.; Redmond, A.; West, R. M.; Morlock, M. M.; Pandit, H. G.
Abstract : Aims: The aim of this study was to estimate the 90-day risk of revision for periprosthetic femoral fracture associated with design features of cementless femoral stems, and to investigate the effect of a collar on this risk using a biomechanical in vitro model. Materials and Methods: A total of 337 647 primary total hip arthroplasties (THAs) from the United Kingdom National Joint Registry (NJR) were included in a multivariable survival and regression analysis to identify the adjusted hazard of revision for periprosthetic fracture following primary THA using a cementless stem. The effect of a collar in cementless THA on this risk was evaluated in an in vitro model using paired fresh frozen cadaveric femora. Results: The prevalence of early revision for periprosthetic fracture was 0.34% (1180/337 647) and 44.0% (520/1180) occurred within 90 days of surgery. Implant risk factors included: collarless stem, non-grit-blasted finish, and triple-tapered design. In the in vitro model, a medial calcar collar consistently improved the stability and resistance to fracture. Conclusion: Analysis of features of stem design in registry data is a useful method of identifying implant characteristics that affect the risk of early periprosthetic fracture around a cementless femoral stem. A collar on the calcar reduced the risk of an early periprosthetic fracture and this was confirmed by biomechanical testing. This approach may be useful in the analysis of other uncommon modes of failure after THA. Cite this article: Bone Joint J 2019;101-B:779–786.